Diplomatic Gatekeeping, Privileges and Immunities - Ola, Temitope (Acta Universitatis Danubius. Relationes Internationales, 2023)
This paper takes a look at the tenacious place of diplomatic gatekeeping in 21st century international relations. Using descriptive methods of qualitative analysis it explores the politico-legal environment within which diplomatic rights and responsibilities emerged. Against the backdrop of the enjoyment of diplomatic privileges and immunities by the representatives of extra-state entities the rationale for the global deployment of diplomat-like personnel by non-state actors is questioned. Aside establishing the nexus between law and practice the paper submits that although diplomatic history is replete with transformations yet the main crux of the leeway granted to diplomatically privileged individuals is to enable foreign Missions perform their functions continuously unhindered.